Reverification of the "resource curse" hypothesis based on industrial agglomeration: Evidence from China. (1st December 2020) - Xue, Yawei; Ye, Xuanting; Zhang, Wei; Zhang, Jian; Liu, Yu; Wu, Chuanbao; Li, Qi
Abstract: Although the "resource curse" hypothesis has been supported by many empirical studies focusing on the transnational and regional levels, there has always been a point of contention about the proper method of estimating and selecting natural resource indicators in literature. This paper proposes a mixed estimation method for panel data of 10 typical oil and gas resource-based cities in China from 1998 to 2015. The results show that resource industry agglomeration can mirror the distribution and dependence on the resource industry by location rather than by merely measuring the influence of the relative scale of resource extraction on economic growth. Using resource industry agglomeration as the main explanatory variable for regional economic growth verifies the resource curse hypothesis and shows the nonlinear characteristics of the negative correlation between resources and economic growth. Despite mostly similar indicator parameter estimates, marked differences exist in measured effects for material capital investments and technological innovation investments. The result of using resource industry agglomeration as the main explanatory variable is basically consistent with the economic theory and is more in line with observed reality than the alternative indicator. The research conclusions can provide evidence and data for index selection in the studies on the mediating effect of resource curse transmission and international comparison.